COST-BENEFIST ANALYSIS OF PV GENERATORS AT RESIDENTIAL BUILDINGS IN THE REGION OF RUSE, BULGARIA - Gabrovska-Evstatieva, Katerina Georgieva; Evstatiev, Boris Ivanov (Journal of Applied Engineering Science, 2017)
In this study a method for cost-benefit analysis of investments in PV generators at residential buildings has been presented. The benefits are evaluated in two categories: financial benefits in terms of net present value of the money and the return on the investment; the ecological benefits presented in saved CO2 emissions in tons and in percentages. A cost-benefit analysis of a PV investment at an apartment in the city of Ruse is presented with different scenarios in terms of installed power. Two risk factors are also evaluated – the buying price of PV energy and the selling price of conventional energy. The obtained results showed that the investment could payback for 6 to 9 years, if the installation is properly sized. The ecological benefits have been evaluated to be approximately 1 t CO2 annually or a reduction of 35% to 42%.